The development of cultural design guidelines for mobile applications for creative industry developers - Muhammad Zulhilmi Samsuri (Tanjong Malim, 2024)
The development of cultural design guidelines for mobile applications for creative industry developers by Muhammad Zulhilmi Samsuri